Exploring MacGuffin Interactions in IoT Smart Objects: A Narrative Approach to Design Education Research. - Lee, Wan‐Chen; Chen, Zi‐Ru; Liang, Rung‐Huei (International Journal of Art & Design Education, 2026)
Internet of Things (IoT) technology has become an integral part of our daily lives, yet its potential for emotional engagement and narrative qualities remains largely unexplored. Objects in films often serve as 'MacGuffins' (elements that may seem unimportant but spark curiosity, drive the plot, and motivate characters), creating suspense and anticipation. This research infuses narrative elements into IoT smart object design, aiming to enhance emotional connections and expand imaginative possibilities. Using the theoretical framework of Object‐Oriented Ontology (OOO), this study emphasises viewing objects as subjects to explore the untapped potential of IoT smart objects. While OOO offers rich conceptual insights, its practical application is hindered by the persistent focus of interaction design on user‐centric frameworks, neglecting the agency and autonomy of objects. To address this, the study develops practical strategies and methodologies that integrate non‐human perspectives without disrupting existing processes. By merging MacGuffin narratives with speculative design principles, interaction workshops using MacGuffin creative cards and ChatGPT foster narrative speculation and innovative smart object proposals. Employing prototyping Design Fiction methods, this study develops strategies that assist educators and help participants grasp speculative design principles more efficiently. This approach enhances participants' interaction design skills while offering a novel and practical method for design education. It also provides a valuable resource for examining the impact of MacGuffin narrative elements on IoT interaction design, enriching future visions of smart objects through fictional writing.